Functional gel cathode strategy to enhance the long-term cyclability of the lithium-polysulfide full cell. (1st April 2022) - Yuan, Yan; Li, Zhengqian; Peng, Xiuping; Xue, Kesi; Liu, Manbo; Fang, Zhao; Wang, Lianli; Du, Huiling; Lu, Hai
Abstract: Lithium-polysulfide (Li-PS) semiflow battery always suffers from a series of drawbacks such as low utilization of active material, inevitable shuttle effect and severe Li corrosion. Herein, a novel PS gel cathode integrating a functional polymer gel network into carbon cloth as the supporting matrix is proposed, in which large quantities of PS species are effectively preserved in the cathode with negligible migration and shuttle. Moreover, the ionically/electronically conductive matrix achieves accelerated redox conversion of the PSs and effective regulation for the nucleation/growth of lithium sulfide. Consequently, the increased reversible capacity, sustainable long-term cycling stability and superior rate capability are demonstrated in the unique cell configuration. Graphical and textual abstract: A unique polysulfide gel cathode architecture, which integrates an optimized polymer gel into the porous carbon cloth substrate as the supporting matrix, actualizing endurable active species immobilization within the cathode and effective regulation for the redox conversion of localized polysulfides. Image, graphical abstract